Reversal Politeology: Interchangeable Use of (im) Politeness in Jordan - Al Soudi, Layth; Ab Rashid, Radzuwan (Dirasat: Educational Sciences, 2021)
This study investigates the interchangeable implementation of (im) polite behavior in light of face theory Specifically, this study explores the way people in Jordan interchangeably implement polite behavior in impolite context to achieve impolite sequel as well as exploring the way people use impolite behavior in polite context. In addition, the study also highlights the role of intentionality and disagreement in language interaction in light of im/politeness considerations. A set of open-ended questionnaires was distributed to twenty-four adults in the city of Maan in Jordan. A thematic analysis approach was used to analyze the data. The findings suggest that impolite behavior within societal constraints does not always lead to negative sequel; rather, it sometimes represents a polite tendency particularly in intimate relationships. Moreover, a polite behavior often represents an implied malicious intention. The study also shows that (im) politeness and face are inseparable due to social considerations of rights and obligations. This study also reveals that disagreement in interaction among interlocutors in Jordan is not a face-threatening act. The study recommends that researchers cast some light on the influence of speech acts on politeness in social interaction.